Microencapsulation of Black Carrot Anthocyanins for Enhanced Thermal Stability - Baysal, Elif; Kazan, Aslihan (My University, 2024)
Pigments obtained from plants and algae are utilized as colour additives in food and pharmaceutical formulations due to the advantages of being non-toxic and possessing several biological activities. However, the low stability limits the utilization of natural pigments and therefore strategies such as chemical modification or encapsulation are required. This study aimed to improve the thermal stability of black carrot anthocyanins by microencapsulation. The effect of parameters such as concentration and flow rate of alginate solution, stirring rate and temperature of CaCl2 solution and needle diameter on the average size, polydispersity (PDI), and sphericity of alginate microparticles were examined. Optimum conditions were elicited as 2% concentration and 1 ml/min flow rate for alginate solution, 40 rpm stirring rate of CaCl2 solution at 4oC and 0.45 mm of needle size resulting in 462.4 ?m of particle size. Heat treatment was also applied and the retention efficiencies were determined as 96.92% and 75.82% for encapsulated and free anthocynanins, respectively. In addition, half-life of anthocyanin rich extract has been shown to increase from 7.5 h to 66.5 h by microencapsulation. These findings indicated the ability of alginate microparticles for the protection of black carrot anthocyanins from thermal degradation and improvement of storage stability.
Keywords: Anthocyanin; Thermal stability; Black carrot; Encapsulation; Alginate microparticles